Papaya Fruit Processing as Meat Tenderizer in Ponggok Village, Blitar - Juwita, Ratna (Journal of Saintech Transfer, 2023)
Papaya is one of the largest commodities in Ponggok Village, Blitar Regency. However, the papaya is only sold and consumed as a fresh fruit. Papaya sap contains protease enzymes (protein decomposers), papain and chymopapain, that can hydrolyze proteins. This protease enzyme is a key factor in increasing protein digestibility and absorption, which in turn affects growth of tissue fibers in meat. These two enzymes can break down the bonds in protein molecules into polypeptides and dipeptides. The purpose of this activity is to provide training on making papain enzymes from papaya fruit. The papain enzyme is used as a meat tenderizer. The target of the training participants was thirty people with the target being PKK women who were members of the Ponggok village farmer group. The method in this training uses the stages of preparation, implementation and evaluation. The survey results show that papaya fruit has not been utilized optimally in Ponggok Village, so it is important to hold training on making papain enzyme from papaya fruit.